2018
DOI: 10.1080/19476337.2018.1513425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrophilic and lipophilic antioxidants from mango peel (Mangifera indica L. cv. Ataulfo) on lipid peroxidation in fish oil

Abstract: 2018) Effect of hydrophilic and lipophilic antioxidants from mango peel (Mangiferaindica L. cv. Ataulfo) on lipid peroxidation in fish oil, CyTA ABSTRACT Antioxidant capacities of hydrophilic (phenolic compounds; H-MPE) and lipophilic (carotenoids; L-MPE) antioxidants from mango peel by ABTS and DPPH assays were determined. The ability of H-MPE and L-MPE to inhibit fish oil peroxidation by the formation of malondialdehyde (MDA) was measured and compared against synthetic antioxidant butylated hydroxytoluene (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The AAI score for gallic acid was the highest, followed by catechin and ascorbic acid compared with one another and Trolox (Trolox). The antioxidant effects of plant samples are linked to their bioactive components, phenolics being the most important [35]. Due to the higher intricacy of flavonoid molecules, the structure-activity correlations (SARs) of flavonoids are frequently more intricate than those of phenolic acids.…”
Section: Hydrophilic and Lipophilic Antioxidant Activity Evaluated By...mentioning
confidence: 99%
“…The AAI score for gallic acid was the highest, followed by catechin and ascorbic acid compared with one another and Trolox (Trolox). The antioxidant effects of plant samples are linked to their bioactive components, phenolics being the most important [35]. Due to the higher intricacy of flavonoid molecules, the structure-activity correlations (SARs) of flavonoids are frequently more intricate than those of phenolic acids.…”
Section: Hydrophilic and Lipophilic Antioxidant Activity Evaluated By...mentioning
confidence: 99%
“…The subsequent extraction of the polyphenols from the remaining residues at the reduced EC and, increased pH could have contributed to a polyphenol extract with lower lipophilic polyphenols but richer in hydrophilic polyphenols in stage 2. Lipophilic polyphenols have been reported to have higher antioxidant capacity when compared to hydrophilic ones 35 . Extraction conditions can therefore be manipulated to obtain two polyphenol extracts with different properties.…”
Section: Resultsmentioning
confidence: 99%
“…Vazquez-Olivo et al [16] also reported that ferulic and p-coumaric acids are the main PCs in corn husk; however, they found lower values of ferulic (455.50 mg/100 g) and p-coumaric (351.550 mg/100 g) acids than the ones reported in our study. These differences could be influenced by environmental, pre-and post-harvest, and drying method conditions [23]. For example, we used a drying temperature of 40 • C, while Vazquez Olivo et al [16] used a drying temperature of 70 • C. Previous reports have indicated that a high temperature can cause PC losses in plants, due to cell wall disruption and rupture, and exposure of PCs to heat, light, and oxygen during drying [24,25].…”
Section: Discussionmentioning
confidence: 99%